Investigation of a wave energy converter with a flywheel and a corresponding generator design - Larsson, Kim (My University, 2012)
A wave energy converter (WEC) with a ywheel have been investigated and suitable generator designs have been proposed and compared. From the uptake of energy from the waves via a buoy to the conversion of mechanical to electrical energy in a generator, this thesis focuses on connecting all the steps on the way. The vertical motion of a buoy, being moved upwards by a wave, exerts a pulling force on a line that connects the buoy to a freewheel; the motion translates to a rotational motion around the axis of the freewheel. The axis connects to a ywheel with a rotational inertia, a gear box and finally a generator. The whole system, except for the buoy, is placed at the bottom of the sea. A 3 meters high and 5 seconds long wave together with an assumed current density for the generator, gives the input data for the generator design. Depending on the use of a ywheel with a large rotational inertia or not and which control strategy is used, the size of the generator vary between a diameter and length of 300 and 410 mm, whilst the maximum electric torque vary between 1350 and 2900 Nm.
Keywords: Elkraftteknik; Electric power engineering